Urban and Disinformation: The Crucial Role of Urban Scale in Addressing Disinformation - Mawaddah, Nur (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Disinformation, particularly during electoral periods, poses significant challenges in urban environments, where high connectivity and dense populations can accelerate the spread of false narratives. This paper examines how disinformation spread during the 2019 elections and explores the role of urban-scale interventions in mitigating its impact. Utilizing social media analysis and social network analysis (SNA), this study uncovers patterns of engagement with disinformation and maps the influence of key actors within urban networks. Findings show that urban areas, due to their social and technological infrastructure, are particularly vulnerable to the effects of misinformation, highlighting the need for targeted urban policy responses.